Kesadaran Masyarakat terhadap Pencegahan Covid-19 serta Penerapan Protokol Kesehatan di Kabupaten Bone Bolango - Muda, Lisdawati; Alwy Satingi, Munandar; Sinalaan, Sanji (Madani: Jurnal Pengabdian Ilmiah, 2021)
Covid-19 (Coronavirus Disease 2019) is a type of disease that has hit the world since the end of 2019 caused by the coronavirus or SARS-CoV-2. This virus spreads from human to human through direct direct contact quickly with symptoms that are only felt a maximum of 14 days after exposure. The entry of covid-19 in Indonesia has made the government take quick and responsive action to prevent and overcome it. The government has provided signs with the issuance of the Decree of the Minister of Health Number HK. 01.07/MENKES/382/2020 Regarding Public Health Protocols in Public Places and Facilities for the Prevention and Control of Coronavirus Disease 2019 (Covid-19). The health minister's decision is a step to minimize the spread of COVID-19 in Indonesia. Community participation in a pandemic situation is the main resource in handling the response. Various forms of contributions and initiatives that have emerged in the community have become part of the handling of the COVID-19 response in the community. Community involvement in handling COVID-19 can be manifested in various forms, including community-based activities, humanitarian volunteers and civil society organizations. Community involvement can accommodate either individually or as an institution by considering the experience, expertise, and mobilization of resources owned